Proximal Left Anterior Descending Artery Treatment Using a Bioresorbable Polymer Coating Sirolimus‐Eluting Stent: Real‐World Outcomes From the Multicenter Prospective e‐Ultimaster Registry. Issue 23 (3rd December 2019) - Codner, Pablo; Saada, Majdi; Sakhov, Orazbek; Polad, Jawed; Malik, Fazila Tun‐Nesa; Munir, Shahzad; Mamas, Mamas; Crowley, Jim; Monsegu, Jacques; Perez, Luis; Kedev, Sasko; Austin, David; et al.
Abstract : Background: Guidelines recommend heart team discussion and coronary artery bypass graft consideration in patients with proximal left anterior descending (LAD) artery stenosis. Evidence suggests that outcomes of proximal LAD angioplasty might not differ from treatment of nonproximal LAD locations. We aim to determine clinical outcomes of patients undergoing percutaneous coronary intervention in the proximal LAD segment in comparison with nonproximal LAD angioplasty, using a thin‐strut drug‐eluting stent. Methods and Results: In this analysis of the e‐Ultimaster registry, patients undergoing angioplasty in the proximal LAD territory were compared with those treated in nonproximal LAD locations. Multivariate analysis and propensity score were used to adjust for differences among the groups. The primary outcome was target lesion failure: a composite of cardiac death, target‐lesion–related myocardial infarction, and/or clinically driven target lesion revascularization at 1‐year follow‐up. Of the 17 805 patients (mean age, 64.2±11; 76% male), 5452 (30.6%) underwent proximal LAD and 12 353 (69.4%) nonproximal LAD percutaneous coronary intervention. Patients in the proximal LAD group had more multivessel disease (48.7% versus 43.5%; P <0.001) and 2‐fold more bifurcations lesions (18.8% versus 9.2%; P <0.0001). After propensity‐weighted adjustment, target lesion failure did not differ between the groups (3.3% versus 2.9%; P =0.17 for proximal LAD versus nonproximal LAD angioplasty, respectively). In multivariate analysis, proximal LAD treatment was not an independent predictor of target lesion failure (odds ratio, 1.07; 95% CI, 0.88–1.31; P =0.48). Conclusions: At 1‐year follow‐up, patients had similar clinical outcomes independent of stenting location, questioning whether proximal LAD treatment should be regarded differently from stenting in any other coronary artery territory.